2007
DOI: 10.1002/cjce.5450850514
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bubble Kinetic Energy on its Bouncing During Collisions with Various Interfaces

Abstract: the canadian Journal of chemical engineering 669Collisions and bouncing of the bubbles with water/gas and water/solid interfaces occurring within a time scale of milliseconds were studied. It was shown that the bubble kinetic energy at the moment of collision has a profound influence on the bubble bouncing prior to the bubble rupture at the liquid/gas interface and attachment to the hydrophobic or remaining arrested beneath hydrophilic solid plates. The mechanism of the bubble bouncing was analyzed and degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 32 publications
4
50
0
2
Order By: Relevance
“…As described elsewhere (Krzan et al, 2004;Malysa et al, 2005;Zawala et al, 2007) at this distance the detached bubble is at the initial (acceleration) stage of the motion and distribution of the adsorption coverage over the bubble surface can be still treated as almost uniform (Jachimska et al, 1998;Krasowska et al, 2007b). Thus, the bubble surface, which formed the bottom interface of the wetting film at the fluorite surface had the positive electrical charge.…”
Section: Collisions and Tpc Formation In The Presence Of N-octyltrimementioning
confidence: 94%
“…As described elsewhere (Krzan et al, 2004;Malysa et al, 2005;Zawala et al, 2007) at this distance the detached bubble is at the initial (acceleration) stage of the motion and distribution of the adsorption coverage over the bubble surface can be still treated as almost uniform (Jachimska et al, 1998;Krasowska et al, 2007b). Thus, the bubble surface, which formed the bottom interface of the wetting film at the fluorite surface had the positive electrical charge.…”
Section: Collisions and Tpc Formation In The Presence Of N-octyltrimementioning
confidence: 94%
“…On the other hand, the changes in the bubble-wall collision dynamics with wall boundary condition have been tested for the normal bouncing on a horizontal top-wall Zawala et al 2007). In these studies, the rising bubble was originally spherical and deformed only when it collided with the horizontal wall.…”
Section: Introductionmentioning
confidence: 98%
“…reported that air pockets trapped on a slippery wall cause the approaching bubble to attach on the wall after a smaller number of bounces than on a no-slip wall. Zawala et al (2007) estimated the transfer of kinetic energy to surface energy during those collisions. In the case of a hydrophobic surface, the energy transfer was small (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported experimental results concerning impingement and subsequent bouncing of a single gas/vapour or liquid bubble on a wall in various fluids [3][4][5][6][7][8][9][10][11][12][13][14]. Many of these authors investigated bubble impact against deformable surfaces, such as the interface between water and air, where coalescence would most likely occur [3,4,[6][7][8]10], while the remaining authors have investigated the effect of a bubble bouncing against solid surfaces [5,9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these authors investigated bubble impact against deformable surfaces, such as the interface between water and air, where coalescence would most likely occur [3,4,[6][7][8]10], while the remaining authors have investigated the effect of a bubble bouncing against solid surfaces [5,9,[12][13][14]. Tsao & Kock [5] observed the interaction between high Email address: donoghdb@tcd.ie (D.B.…”
Section: Introductionmentioning
confidence: 99%